Performance Evaluation Learning and Growth Perspective Balai Pengawas Obat Dan Makanan Jambi - Rahmat Hidayat; Marchaban Marchaban; Sumarni Sumarni (Faculty of Pharmacy, Universitas Gadjah Mada)
Balai POM of Jambi is obliged to act professional and improve the organization’s performance in order to serve the society. Learning and growth perspective is set to get outcome advantage for other third perspective Balanced Scorecard. The purpose of this research was to evaluate learning and growth perspective in Balai POM Jambi, while also determining facilitating and obstructing factors in this perspective. The research was conducted in descriptive method with qualitative and quantitative data gathered from secondary data provided by Balai POM Jambi in 2015 to 2016. Data was gathered using questionnaire and interview. Qualitative and quantitative descriptive analysis were performed by comparing target performance with real achieved performance for each indicators then referring to the standard. Interviews was conducted to determine facilitating and obstructing factors in achieving the best performance. The result of this study in performance learning and growth perspective for human capital result is good; organizational capital results is moderate; informational capital results is moderate. Facilitating factors learning ang growth perspective of Balai POM Jambi were budget plan, competency staff, organizational capital, implementation management information system, implementation QMS, guidance, reward and punishment. Obstructing factors were limitation in human resources and facilities. In general term, performance learning and growth perspective need to be improved, by improving leadership and facilities in Balai POM Jambi.